2012
DOI: 10.3892/mmr.2012.862
|View full text |Cite
|
Sign up to set email alerts
|

Differential signature of fecal microRNAs in patients with pancreatic cancer

Abstract: Abstract. The potential value of microRNAs as new biomarkers for pancreatic cancer (PCa) screening was explored in this study. Fecal microRNAs from stool samples obtained from 29 PCa patients, 22 chronic pancreatitis (CP) patients and 13 normal individuals were extracted, and 7 microRNAs (miR-16, miR-21, miR-155, miR-181a, miR-181b, miR-196a and miR-210) were detected. miR-181b and miR-210 discriminated PCa from normal individuals with receiver operating characteristic (ROC) curves and area under curve (AUC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Next, we found that 21 studies were performed in Asian populations and the other 15 studies were performed in Caucasian populations. A total of 25 studies detected miRNA in blood (such as whole blood [24, 26, 28], serum [9, 20, 22, 23, 27, 29, 32, 34] and plasma samples [2, 8, 10, 11, 13, 15, 16, 18, 19, 25, 35]), and 11 studies detected miRNA in non-blood samples (including bile [13], cyst fluid [17], pancreatic juice [12, 30], salivary [7, 33], and stool [21, 31]). We evaluated 19 studies for assessing the diagnostic efficacy of multiple miRNAs [2, 13, 15, 1722, 2632, 34] and single miRNAs using meta-analysis for discriminating patients with PaCa from healthy controls in 17 studies [712, 16, 2325, 33, 35] in these 29 articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we found that 21 studies were performed in Asian populations and the other 15 studies were performed in Caucasian populations. A total of 25 studies detected miRNA in blood (such as whole blood [24, 26, 28], serum [9, 20, 22, 23, 27, 29, 32, 34] and plasma samples [2, 8, 10, 11, 13, 15, 16, 18, 19, 25, 35]), and 11 studies detected miRNA in non-blood samples (including bile [13], cyst fluid [17], pancreatic juice [12, 30], salivary [7, 33], and stool [21, 31]). We evaluated 19 studies for assessing the diagnostic efficacy of multiple miRNAs [2, 13, 15, 1722, 2632, 34] and single miRNAs using meta-analysis for discriminating patients with PaCa from healthy controls in 17 studies [712, 16, 2325, 33, 35] in these 29 articles.…”
Section: Resultsmentioning
confidence: 99%
“…In multiple miRNA assays, miR-21 [7, 11, 12, 15, 1720, 23, 31], miR-155 [12, 13, 15, 18, 19, 31] and miR-210 [15, 18, 19, 21, 30] were used most frequently in the included studies. Moreover, we further found that the diagnostic accuracy of miRNAs to differentiate PDAC from controls (SEN:87%, SPE: 86%, AUC: 0.93) indicating a higher accuracy compared with applications on PaCa patients (SEN: 80%, SPE:83%, AUC: 0.86) (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Ren et al evaluated the miRNA signature (miR-16, -21, -155, -181a, -181b, -196a and -210) in stool samples collected from PC (n = 29) and CP (n = 22) patients, and healthy controls (n = 13). Among these, miR-181b and -210 discriminated PC from normal individuals with receiver operator characteristic curves and AUCs of 0.745 and 0.772, respectively, and a significant correlation was observed between tumor diameter and miR-196a expression (Spearman’s rank: 0.516; p = 0.041) [73]. While looking for an miRNA profile for the early detection of PC, Yu et al , in a comprehensive miRNA analysis, evaluated 700 miRNAs in PanIN lesions via quantitative real-time PCR.…”
Section: Screening Strategiesmentioning
confidence: 99%
“…There were 80 studies that detected miRNAs in the blood (such as whole blood [ 14 , 46 , 53 , 54 ], serum [ 24 , 27 , 28 , 30 , 32 , 39 , 40 , 50 , 51 ], and plasma samples [ 3 , 11 – 13 , 21 , 23 , 26 , 33 , 34 , 36 – 38 , 52 ]), and 29 studies detected miRNA in nonblood samples (including tissues [ 41 43 , 45 , 47 49 , 55 ], pancreatic juice [ 44 ], and stool [ 22 , 25 , 31 , 35 ]). We included 71 studies to evaluate the diagnostic efficacy of single miRNAs [ 12 , 13 , 21 , 22 , 26 – 29 , 33 , 34 , 36 , 38 , 39 , 41 43 , 47 , 54 , 55 ] and multiple miRNAs [ 11 , 14 , 23 25 , 30 – 32 , 35 , 37 , 40 , 44 46 , 48 53 ] for distinguishing patients with PaC from controls in 38 studies. The selected studies adopted the reverse transcription polymerase chain reaction (RT-PCR) or immunohistochemistry (IHC) method...…”
Section: Resultsmentioning
confidence: 99%